Of men and herds in barrenland prehistory ... - Gordon, Bryan H. C. (University of Calgary, 1974)
Bibliography: p. 300-317. ... : This thesis represents an attempt at elucidating the temporal and spatial interrelationships between barrenland cultures, climates and caribou herds. Its core is in the form of a case study, that of the prehistoric interaction of the human hunting bands, climatic effects and caribou herd distributions in the Canadian barrenlands during the Arctic Small Tool tradition occupation after 1500 B.C. Following initial descriptions of barrenland geography, biology, geology, climatology and ethnology, site locations resulting from the hunter and prey relationship are ex-plored. Basic to this relationship and site locations are two primary suppositions. They are: (1) caribou herds are discrete, their separateness b.?se.d upon environment and behavior; and (2) the hunting soci.eties who prey upori. the caribou tend to be discrete due to their alignment with discrete herds. Three corollaries follow the suppositions: (1) band movements and human communication are usually confined to herd migration corridors and forage ...